Research on the Flexibility Margin of an Electric–Hydrogen Coupling Energy Block Based on Model Predictive Control - Han, Zijiao; Yuan, Shun; Dong, Yannan; Ma, Shaohua; Bian, Yudong; Mao, Xinyu (Frontiers in Energy Research, 2022)
Hydrogen energy plays an important role in the transformation of low-carbon energy, and electric–hydrogen coupling will become a typical energy scenario. Aiming at the operation flexibility of a low-carbon electricity–hydrogen coupling system with high proportion of wind power and photovoltaic, this work studies the flexibility margin of an electricity–hydrogen coupling energy block based on model predictive control. By analyzing the power exchange characteristics of heterogeneous energy, the homogenization models of various heterogeneous energy sources are established. According to the analysis of power system flexibility margin, three dimensions of flexibility margin evaluation indexes are defined from the dimension of system operation, and an electricity–hydrogen coupling energy block scheduling model is established. The model predictive control algorithm is used to optimize the power balance operation of the electro–hydrogen coupling energy block, and the flexibility margin of the energy block is quantitatively analyzed and calculated. Through the example analysis, it is verified that the calculation method proposed in this article can not only realize the online power balance optimization of the electric–hydrogen coupling energy block but also effectively quantify the operation flexibility margin of the electric–hydrogen coupling energy block.